A aventura de estar no mundo: uma forma de vida em Drummond - Samuel Rezende Moreira (2022)
I aim to discuss part of the Carlos Drummond de Andrade’s poetry, based on three axes which comprehend “subject”, “language”, and “world”. From there, I identify in the author poems a life structured by the connection of certain matrixes of ideas, such as “abandon”, “adventure”, “fate”, and “liberty”. My interpretation broaches five poems, which are representatives of what I want to show in Drummond’s work. These poems are “Seven-sided Poem” and “Politics”, both from Some Poetry (1930), “Gesture and word”, from Oxtime (1968/1973/1979), “Stanzas”, from New Poems (1948), and “Brazilian chant”, from Impurities of the Blank (1973). The matrixes founded out indicate by the synchronic reading the characterization of a reflexive and speculative “form of life”, in which the elements of the poetic language become decisive for the interpretation. Thus, it will be possible to explore and discover new associations in the poems.